2007
DOI: 10.2495/cmem070011
|View full text |Cite
|
Sign up to set email alerts
|

Direct simulations of fluid dynamic sounds by the finite difference lattice Boltzmann method

Abstract: In this paper we present some applications of the finite difference lattice Boltzmann method (FDLBM) to direct simulations of fluid dynamic sound. The Arbitrary Lagrangian Eulerian formulation is introduced to FDLBM and the sounds emitted from moving bodies are successfully simulated. The two-particle model is used to simulate two-phase flows, and introducing a fluid elasticity the sound propagation inside the liquid is simulated. The sounds generated on the interface between the liquid and gas are also succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The described LBM approach recovers the compressible Navier-Stokes equation. More details of the discrete BGK formulation and numerical procedure are referred to [8].…”
Section: Discrete Bgk Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…The described LBM approach recovers the compressible Navier-Stokes equation. More details of the discrete BGK formulation and numerical procedure are referred to [8].…”
Section: Discrete Bgk Equationmentioning
confidence: 99%
“…Tsutahara et al [8] have reported successful applications of the finite difference lattice Boltzmann method (FDLBM) to the direct numerical simulation of the sound generated a body immersed in fluids. Akamatsu et al [9] has demonstrated that the FDLBM is also a useful approach for studying problems in the non-linear acoustics.…”
Section: Introductionmentioning
confidence: 99%